Effects of Ocean Ecosystem on Marine Aerosol-Cloud Interaction. (20th June 2010) - Meskhidze, Nicholas; Nenes, Athanasios
Abstract : Using satellite data for the surface ocean, aerosol optical depth (AOD), and cloud microphysical parameters, we show that statistically significant positive correlations exist between ocean ecosystem productivity, the abundance of submicron aerosols, and cloud microphysical properties over different parts of the remote oceans. The correlation coefficient for remotely sensed surface chlorophyll a concentration ([Chl- a ]) and liquid cloud effective radii over productive areas of the oceans varies between− 0.2 and− 0.6 . Special attention is given to identifying (and addressing) problems from correlation analysis used in the previous studies that can lead to erroneous conclusions. A new approach (using the difference between retrieved AOD and predicted sea salt aerosol optical depth, AOD diff ) is developed to explore causal links between ocean physical and biological systems and the abundance of cloud condensation nuclei (CCN) in the remote marine atmosphere. We have found that over multiple time periods, 550 nmAOD diff (sensitive to accumulation mode aerosol, which is the prime contributor to CCN) correlates well with [Chl- a ] over the productive waters of the Southern Ocean. Since [Chl- a ] can be used as a proxy of ocean biological productivity, our analysis demonstrates the role of ocean ecology in contributing CCN, thus shaping the microphysical properties of low-level marine clouds.